The Role of Principal Leadership in Improving Teacher Performance at SMP Negeri 2 Kolaka - Faisal, Andi; Saputra, Ade; Ramadhan, Muh.; Mukmin, Mukmin (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The principal plays a strategic role in improving the quality of education, particularly through leadership that impacts teacher performance. Teacher performance is an important indicator of the success of the learning process in schools and is greatly influenced by the principal's ability to carry out his/her duties and functions effectively. This study aims to describe the implementation of the principal's duties and functions, the condition of teacher performance, and the principal's role in improving teacher performance at SMP Negeri 2 Kolaka. This study uses a qualitative approach with a descriptive research type. The research subjects included the principal, vice principal, and several teachers. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results of the study indicate that the principal of SMP Negeri 2 Kolaka has carried out his/her duties and functions well, particularly in the aspects of leadership, coaching, supervision, and motivating teachers. Teacher performance is demonstrated through discipline, implementation of learning, and active participation in professional development activities. The principal's role in improving teacher performance is realized through the implementation of work discipline, continuous coaching, providing opportunities to participate in professional development activities, and creating a conducive work climate. This study concludes that principal leadership has an important contribution in improving teacher performance and supporting the achievement of educational goals in schools.